2013
DOI: 10.1097/fpc.0b013e328361d4bb
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of tapasin polymorphisms with aspirin-exacerbated respiratory disease in asthmatics

Abstract: TAPBP polymorphisms may play a role in the development of AERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Moreover, in a Chinese population, the rs9277972 was associated with an increased risk for hepatitis C virus [43]. On the other hand, the rs2071888 (SNP-associated in our study) has only been linked with gastrointestinal stromal tumors [44] and aspirin-exacerbated respiratory disease [45].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Moreover, in a Chinese population, the rs9277972 was associated with an increased risk for hepatitis C virus [43]. On the other hand, the rs2071888 (SNP-associated in our study) has only been linked with gastrointestinal stromal tumors [44] and aspirin-exacerbated respiratory disease [45].…”
Section: Discussioncontrasting
confidence: 50%
“…There are no previous studies where rs2071888 has been associated with influenza A/H1N1 or another viral infection. The rs2071888 is a missense variant in the TAPBP exon 4, which generates a Threonine > Arginine change, which could alter the polarity of the protein structure, thereby modulating interactions with other molecules such as the HLA class I, leading to an altered antigen presentation and consequently, deficient infected cells clearance by CD8+ T cells, higher viral replication, and disease development [45]. In this sense, we conducted a bioinformatics analysis where we found that the rs2071888/G allele decreases the affinity for a transcriptional factor, affecting the TAPBP expression, probably leading to a deficient antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…While a reduction in TAPBP expression has been associated to tumor progression in colorectal cancer and chronic hepatitis B [ 41 , 42 ], the rs2071888 SNP has been associated with wild type gastrointestinal tumors and gallbladder cancer [ 43 , 44 ]. Furthermore, asthmatic patients carrying the CG and GG genotypes may have a higher decline in forced expiratory volume in 1 s after aspirin provocation when compared to those patients carrying the GG genotype [ 45 ]. Finally, the SLC47A2 gene is involved in the excretion of toxic electrolytes in urine and bile [ 46 ], and its rs12943590 SNP has been largely found to be involved in the pharmacodynamics of metformin and pharmacogenetics of type II diabetes mellitus [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A SNP in PSORS1C1 was associated with allopurinol-induced severe adverse reactions 29,30 . SNPs in HSP70, TAPBP, and WDR46 were found to be associated with aspirinexacerbated respiratory disease [31][32][33] .…”
Section: Gwas For Covid-19 Vaccine Adverse Eventsmentioning
confidence: 99%